2008
DOI: 10.1007/s00259-008-0793-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relationship between coronary vasodilator reserve assessed by 82Rb PET imaging and coronary artery stenosis severity

Abstract: The relationship between myocardial blood flow (MBF) and stenosis severity has been determined previously using cyclotron-produced radiotracers such as 15 O-H 2 O and 13 N-ammonia. An attractive alternative to overcome the limitations related to the use of cyclotron might be to use the generator-produced Rubidium-82 as a flow tracer. The current study was undertaken to investigate the relationship between MBF and coronary vasodilator reserve (CVR) as measured by Rubidium-82 positron emission tomography (PET) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…[85][86][87] • In general, hyperemic MBF and MFR are relatively preserved for coronary lesions with less than 70% angiographic stenosis or with preserved fractional flow reserve (FFR) ([ 0.8). 45,47,51,52,[85][86][87][88][89]91,141,142 However, both Figure 7. Receiver-operator characteristic curves for detection of severe CAD using MFR.…”
Section: Reporting Quantitative Mbf Datamentioning
confidence: 99%
See 1 more Smart Citation
“…[85][86][87] • In general, hyperemic MBF and MFR are relatively preserved for coronary lesions with less than 70% angiographic stenosis or with preserved fractional flow reserve (FFR) ([ 0.8). 45,47,51,52,[85][86][87][88][89]91,141,142 However, both Figure 7. Receiver-operator characteristic curves for detection of severe CAD using MFR.…”
Section: Reporting Quantitative Mbf Datamentioning
confidence: 99%
“…85 Though initially established using 15 O-water, this finding was quickly replicated using 13 N-ammonia [86][87][88] and more recently using 82 Rb. 89,90 The application of stress MBF and MFR for improving the diagnostic accuracy of PET MPI with clinical protocols has been investigated by many groups with both 13 N-ammonia 47,48,88 and 82 Rb. 52, 91 Although these studies have consistently demonstrated improved diagnostic sensitivity (case example in Figure 6), at least 2 large studies have raised concerns about potential for decreased specificity (Figure 7), 52,91 possibly due to the contributions of diffuse atherosclerosis and microvascular disease to stress MBF and MFR measurements.…”
Section: Cad Diagnosismentioning
confidence: 99%
“…In the study by Anagnostopoulos et al 22 linearity with the However, in all tracers except 15O-water, the tracer extraction is reduced when perfusion is increased leading to underestimation of perfusion if only tracer uptake is used.…”
Section: Interpretation Of Absolute Myocardial Perfusion Resultsmentioning
confidence: 96%
“…5 As regard to absolute perfusion in mL/g/minute, a little clinical evidence is available and it also appears that different traces may provide different cutoffs. 15,[21][22][23] In the study by Muzik et al 5 using 13 N-ammonia as tracer, the optimal cutoff value was found to be quite low (1.52 mL/g/minute) to separate ischemic from noninschemic regions. In our recent analysis using 15 O-water the ideal cutoff for absolute stress perfusion was 2.5 mL/g/minute, the range from 2.0 to 2.5 being mildly reduced.…”
Section: Interpretation Of Absolute Myocardial Perfusion Resultsmentioning
confidence: 99%
“…In a recent study with 82 Rb PET/ CT, the diagnostic sensitivity and specificity were 93% and 83%, respectively (35); in particular, the accuracy for detecting multivessel CAD was exceedingly high. Major advantages of the use of myocardial perfusion PET are the abilities to quantify measures of absolute blood flow and to define areas of dampened coronary flow reserve (36). The addition of nonperfusion findings, such as changes in the left ventricular ejection fraction, and the addition of a CAC scan can further improve the detection of CAD by PET (13).…”
Section: Diagnostic Accuracy Of Spect and Petmentioning
confidence: 99%